Full-Thickness Eyelid Lesions in Sarcoidosis - Megan E. Collins; Vesna Petronic-Rosic; Nadera J. Sweiss; Marcus M. Marcet (Case Reports in Ophthalmological Medicine)
Eyelid involvement in sarcoidosis is very rare. A search of the medical literature indicates one previous report of sarcoidosis with destructive eyelid lesions. We describe the case of a 50-year-old woman with severe systemic sarcoidosis, which included her eyelids. To our knowledge, the case presented herein represents the first to show the full-thickness histopathology of destructive eyelid lesions in sarcoidosis.